HASIL BELAJAR KETERAMPILAN MENULIS BAHASA JERMAN MENGGUNAKAN MEDIA PEMBELAJARAN BUCHSTABENSALAT SISWA KELAS X MIA 1 SMA NEGERI 8 SURABAYA - NURUSSHOBA, (LATERNE, 2016)
There are four skills in the German language learning, writing skills, listening skills, reading skills and speaking skills. Writing skills is a thought and an idea that was applied in a good writing. In the language learning, writing skills is a language components that are active and productive. We can use any methode to get student?s attention, like with media. The main purpose of using media in learning activities is to increase student?s writing skills. Buchstabensalat is a seeking word game which contain some random alphabets. The students must find the right arrangement of letters to be a right word. Buchstabensalat can sharpen the brain and it is fun. In this application, Buchstabensalat media can be done individually or in small group. The research problem of this study is ?How does the students? study result through Buchstabensalat media in teaching writing skill in German to the students class X MIA 1 SMAN 8 Surabaya??. The aim of this study is describing the study result of students through Buchstabensalat media in teaching writing skill in German lesson to the students class X MIA 1 SMAN 8 Surabaya. This study used descriptive qualitative approach. It was done four times of meeting. The data gained of this study is test result of students? descriptive writing using Buchstabensalat media. Instrument of this study is a test. The data is analyzed. The number of students are 42 students.during the four times of meeting, the students are given learning by using Buchstabensalat media. The conclusions of this study is the result of this study showed that the students? score were increased after applying with Buchstabensalat as media. This result was showed from the total score of students? study result in the first test (invidual test) is 126. The total score of students? study result in the second test (invidual test) is 228. The total score of students? study result in the first test (group test) is 210. The total score of students? study result in the second test (group test) is 246. So that, Buchstbensalat media can be use as alternative of learning media for writing skills in class X MIA 1 SMAN 8 Surabaya. Keywords: Writing Skill, Buchtabensalat Media.